Phagotrophy in Photosynthetic Eukaryotic Microbes from Polar Environments - McKie-Krisberg, Zaid Mahira (Temple University Libraries, 2014)
Biology Ph.D. Polar regions impose harsh conditions, including low temperatures, and prolonged periods of darkness on resident microbial communities. Despite these challenges, the conditions in these environments can also create opportunities for organisms utilizing combined trophic strategies (Mixotrophy). Only a limited number of studies have identified mixotrophic behavior in polar microbial eukaryotes, and even fewer studies have quantified the response of mixotrophs to likely environmental drivers of trophic behavior (light and nutrients). The goal of this work is to provide an identification of mixotrophic behavior and elucidate of some of the factors that influence algae isolated from polar environments. First, a study of the Arctic prasinophyte, Micromonas pusilla is presented in the first species-specific identification of mixotrophy in a eukaryotic phytoflagellate of this size class. M. pusilla grazed on bacteria under all experimental conditions, responding to nutrient limitation with increased rates of bacterivory. M. pusilla also showed evidence of prey selection. In contrast to the phagotrophic response, photosynthetic production was decreased under low-nutrient conditions. In an additional study of microbial eukaryotes from the Antarctic environment, identification of phagotrophy in photosynthetic nanoflagellates representing multiple evolutionary lineages: Cryptophyceae (Geminigera cryophila) and Prasinophyceae (Pyramimonas tychotreta and Mantoniella antarctica), showed that mixotrophy is more widespread in the Southern ocean that previously thought. G. cryophila and M. antarctica increased ingestions in dark treatments, but did not respond to difference in nutrient concentrations. In contrast, no significant grazing activity was observed in P. tychotreta under high nutrient conditions. When nutrients were reduced, ingestion of bacteria by P. tychotreta was observed and grazing increased in dark as compared to illuminated treatments. Finally, through a series of experimental assays, the ...